2009
DOI: 10.1007/s10661-009-0911-z
|View full text |Cite
|
Sign up to set email alerts
|

Using dual classifications in the development of avian wetland indices of biological integrity for wetlands in West Virginia, USA

Abstract: Considerable resources are being used to develop and implement bioassessment methods for wetlands to ensure that "biological integrity" is maintained under the United States Clean Water Act. Previous research has demonstrated that avian composition is susceptible to human impairments at multiple spatial scales. Using a site-specific disturbance gradient, we built avian wetland indices of biological integrity (AW-IBI) specific to two wetland classification schemes, one based on vegetative structure and the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…In September and October of 2007, we collected four litter types (broadleaf cattail Typha latifolia L., common rush Juncus effusus L., brookside alder Alnus serrulata (Ait.) Willd., and reed canary grass Phalaris arundinacea L.) which were chosen because they are common, dominant wetland plant species in West Virginia (Balcombe et al 2005;Veselka IV 2008). Litter mixes can have non-additive decomposition rates compared to single species (Gartner & Cardon 2004), so a fifth litter type was created with a mixture (3:2:1) of reed canary grass, common rush, and brookside alder to approximate ratios of plant species present in the wetlands (Balcombe et al 2005).…”
Section: Decomposition Proceduresmentioning
confidence: 99%
“…In September and October of 2007, we collected four litter types (broadleaf cattail Typha latifolia L., common rush Juncus effusus L., brookside alder Alnus serrulata (Ait.) Willd., and reed canary grass Phalaris arundinacea L.) which were chosen because they are common, dominant wetland plant species in West Virginia (Balcombe et al 2005;Veselka IV 2008). Litter mixes can have non-additive decomposition rates compared to single species (Gartner & Cardon 2004), so a fifth litter type was created with a mixture (3:2:1) of reed canary grass, common rush, and brookside alder to approximate ratios of plant species present in the wetlands (Balcombe et al 2005).…”
Section: Decomposition Proceduresmentioning
confidence: 99%
“…However, due to the number of sites used in this study (151), we are confident we adequately sampled the major HGM classes found in West Virginia ( Fig. 1; Veselka et al 2009). We categorized wetlands by both the Cowardin and regional HGM subclass (Cole et al 1997) type (Table 1).…”
Section: Methodsmentioning
confidence: 93%
“…We stratified sampling across both wetland Cowardin classes and the major US Environmental Protection Agency's Level 3 aquatic ecoregions within West Virginia, USA: the Central Appalachians, the Ridge and Valley, and the Western Allegheny Plateau (Omernik 1987;Woods et al 1999) by targeting previously studied wetlands (Balcombe et al 2005) and selecting random 7.5-min quadrangles using a Geographic Information System database (Veselka et al 2009). We conducted "reconnaissance" on the random quadrangles, selecting accessible sites that did not require extensive property ownership investigations or permissions due to project constraints.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations